EFECTS OF CHEMICAL COMPOSITION ON THE MICROSTRUCTURE AND PROPERTIES OF THE CU-Ge-Sb ALLOYS - Dejan Gurešić; Aleksandar Đorđević; Aleksandar Marković; Milica Tomović; Nadežda Talijan; Ivana Manasijević (Journal of Engineering & Processing Management, 2016)
In the current study a ternary Cu-Ge-Sb system has been experimentally assessed. Chemical andphase compositions of the alloy samples from three vertical sections Cu-GeSb, Ge-CuSb and Sb-CuGe were studied using scanning electron microscopy (SEM) and energy dispersive spectroscopy(EDS) and confirmed by X-ray diffraction analysis (XRD). Hardness of the alloys was measured byBrinell method while hardness of phases was measured using micro Vickers method. Electricalconductivity of the studied alloys was measured using eddy current instrument. Based onexperimentally determined values iso-lines of hardness and electrical conductivity for the wholeternary system were calculated using assumed mathematical models.
Keywords: ternary Cu-Ge-Sb system; microstructural investigation; hardness test; electrical conductivity